Cannabis-related diagnosis in pregnancy and adverse maternal and infant outcomes. (1st August 2021) - Bandoli, Gretchen; Jelliffe-Pawlowski, Laura; Schumacher, Benjamin; Baer, Rebecca J.; Felder, Jennifer N.; Fuchs, Jonathan D.; Oltman, Scott P.; Steurer, Martina A.; Marienfeld, Carla
Highlights: Increasing prevalence of cannabis-related diagnosis (CRD) from 2011 to 2017. Increased risk of all maternal and infant outcomes assessed from CRD. Strongest effects for prematurity and gastrointestinal malformations. Stronger effects when another substance-related diagnosis accompanied CRD. Abstract: Background: Cannabis use and cannabis use disorders are increasing in prevalence, including among pregnant women. The objective was to evaluate the association of a cannabis-related diagnosis (CRD) in pregnancy and adverse maternal and infant outcomes. Methods: We queried an administrative birth cohort of singleton deliveries in California between 2011–2017 linked to maternal and infant hospital discharge records. We classified pregnancies with CRD from International Classification of Disease codes. We identified nicotine and other substance-related diagnoses (SRD) in the same manner. Outcomes of interest included maternal (hypertensive disorders) and infant (prematurity, small for gestational age, NICU admission, major structural malformations) adverse outcomes. Results: From 3, 067, 069 pregnancies resulting in live births, 29, 112 (1.0 %) had a CRD. CRD was associated with an increased risk of all outcomes studied; the strongest risks observed were for very preterm birth (aRR 1.4, 95 % CI 1.3, 1.6) and small for gestational age (aRR 1.4, 95 % CI 1.3, 1.4). When analyzed with or without co-exposure diagnoses, CRD alone conferred increased risk for all outcomes compared to no use. The strongest effects were seen for CRD with other SRD (preterm birth aRR 2.3, 95 % CI 2.2, 2.5; very preterm birth aRR 2.6, 95 % CI 2.3, 3.0; gastrointestinal malformations aRR 2.0, 95 % CI 1.6, 2.6). The findings were generally robust to unmeasured confounding and misclassification analyses. Conclusions: CRD in pregnancy was associated with increased risk of adverse maternal and infant outcomes. Providing education and effective treatment for women with a CRD during prenatal care may improve maternal and infant health.